Thematic analysis of barriers and facilitators to implementation of neonatal resuscitation guideline changes - Lee, Henry C. (J Perinatol, 2016)
OBJECTIVE: To evaluate experiences regarding implementation of Neonatal Resuscitation Program (NRP) guideline changes in the context of a collaborative quality improvement (QI) project. STUDY DESIGN: Focus groups were conducted with local QI leaders and providers from 9 sites that participated in a QI collaborative. Thematic analysis identified facilitators and barriers to implementation of NRP guideline changes and quality improvement in general. RESULTS: Facilitators for QI included comparative process measurement and data tracking. Barriers to QI were shifting priorities and aspects of the project that seemed inefficient. Specific to NRP, implementation strategies that worked involved rapid feedback, and education on rationale for change. Changes that interrupted traditional workflow proved challenging to implement. Limited resources and perceptions of increased workload were also barriers to implementation. CONCLUSIONS: Collaborative QI methods are generally well accepted, particularly data tracking, sharing experience, and education. Strategies to increase efficiency and manage workload may facilitate improved staff attitudes toward change.